DNA barcoding identifies cryptic animal tool materials - Steele, Matthew P.; Neaves, Linda E.; Klump, Barbara C.; St Clair, James J. H.; Fernandes, Joana R. S. M.; Hequet, Vanessa; Shaw, Phil; Hollingsworth, Peter M.; Rutz, Christian (Proceedings of the National Academy of Sciences - PNAS, 2021)
Some animals fashion tools or constructions out of plant materials to aid foraging, reproduction, self-maintenance, or protection. Their choice of raw materials can affect the structure and properties of the resulting artifacts, with considerable fitness consequences. Documenting animals’ material preferences is challenging, however, as manufacture behavior is often difficult to observe directly, and materials may be processed so heavily that they lack identifying features. Here, we use DNA barcoding to identify, from just a few recovered tool specimens, the plant species New Caledonian crows (Corvus moneduloides) use for crafting elaborate hooked stick tools in one of our long-term study populations. The method succeeded where extensive fieldwork using an array of conventional approaches—including targeted observations, camera traps, radio-tracking, bird-mounted video cameras, and behavioral experiments with wild and temporarily captive subjects—had failed. We believe that DNA barcoding will prove useful for investigating many other tool and construction behaviors, helping to unlock significant research potential across a wide range of study systems.